Two interfacial collinear Griffith cracks in thermo-elastic composite media - Mishra, P.K.; Das, S. (Serbian Society of Heat Transfer Engineers, 2018)
The objective of the article is to find the stress intensity factors and crack energy for a pair of collinear Griffith cracks situated at the interface of the two orthotropic materials under steady-state temperature field. The problem is reduced to a pair of singular integral equations, which are solved using Jacobi's polynomials. Numerical computations are carried out for two different pairs of orthotropic materials for different particular cases, which are depicted through figures. The effect of material constants and temperature coefficients on the behavior of physical quantities viz., stress intensity factors and crack energy of the interfacial cracks is the key feature of the present article. © 2017 Society of Thermal Engineers of Serbia.
Keywords: INTERFACIAL; THERMO-ELASTIC; COMPOSITE